Identification and validation of number of pod ‐ and seed ‐ related traits QTLs in soybean. (23rd August 2018) - Li, Candong; Zou, Jianan; Jiang, Hongwei; Yu, Jingyao; Huang, Shiyu; Wang, Xinyu; Liu, Chunyan; Guo, Tai; Zhu, Rongsheng; Wu, Xiaoxia; Hu, Zhenbang; Wang, Zhixin; et al.
Abstract: Traits related to the number of pods and seeds are important yield factors on soybean. The relationships between phenotype and quantitative trait loci (QTLs) of these traits may reveal the mechanisms underlying productivity. Our study objectives were to analyse phenotypic correlations, detect stable QTLs and identify candidate genes useful for marker‐assisted selection. Phenotypic analyses revealed that NThSP (number of three‐seeded pods) was positively correlated with NPPP (number of pods per plant) and SNPP (number of seeds per plant). Seventy‐five QTLs were identified based on the mean phenotypic data for at least 2 years. We detected two to 15 and one to three significant QTLs identified at the same location, respectively. Six consensus QTLs associated with at least two NPS‐related (number of pods and seeds related) traits were identified. Two of these were verified in another population. The QTLs for NPPP, SNPP and NThSP formed a consensus QTL cluster on GM02. Another 27 QTLs also formed clusters in five regions. Fifteen candidate genes were mined and discussed. The results will provide more information to soybean breeding.